Wide Distribution of Foxicin Biosynthetic Gene Clusters in Streptomyces Strains – An Unusual Secondary Metabolite with Various Properties - Greule, Anja; Marolt, Marija; Deubel, Denise; Peintner, Iris; Zhang, Songya; Jessen-Trefzer, Claudia; De Ford, Christian; Burschel, Sabrina; Li, Shu-Ming; Friedrich, Thorsten; Merfort, Irmgard; Lüdeke, Steffen; et al. (Frontiers in Microbiology, 2017)
Streptomyces diastatochromogenes Tü6028 is known to produce the polyketide antibiotic polyketomycin. The deletion of the pokOIV oxygenase gene led to a non-polyketomycin-producing mutant. Instead, novel compounds were produced by the mutant, which have not been detected before in the wild type strain. Four different compounds were identified and named foxicins A–D. Foxicin A was isolated and its structure was elucidated as an unusual nitrogen-containing quinone derivative using various spectroscopic methods. Through genome mining, the foxicin biosynthetic gene cluster was identified in the draft genome sequence of S. diastatochromogenes. The cluster spans 57 kb and encodes three PKS type I modules, one NRPS module and 41 additional enzymes. A foxBII gene-inactivated mutant of S. diastatochromogenes Tü6028 ΔpokOIV is unable to produce foxicins. Homologous fox biosynthetic gene clusters were found in more than 20 additional Streptomyces strains, overall in about 2.6% of all sequenced Streptomyces genomes. However, the production of foxicin-like compounds in these strains has never been described indicating that the clusters are expressed at a very low level or are silent under fermentation conditions. Foxicin A acts as a siderophore through interacting with ferric ions. Furthermore, it is a weak inhibitor of the Escherichia coli aerobic respiratory chain and shows moderate antibiotic activity. The wide distribution of the cluster and the various properties of the compound indicate a major role of foxicins in Streptomyces strains.